PS 17-51 VISIT-TO-VISIT BLOOD PRESSURE VARIABILITY AND CHRONIC KIDNEY DISEASE IN TYPE 2 DIABETES PATIENTS IN GHANA. (September 2016) - Yeboah, Kwame; Yorke, Ernest; Konlan, Kennedy
Abstract : Objective: Visit-to-visit blood pressure (BP) variability is an important predictor cardiovascular diseases. In this study, we investigated association between visit-to-visit BP variability and chronic kidney disease (CKD) in type 2 diabetes (T2DM) patients in Ghana. Design and method: An average of 6 BP measurements from 282 T2DM patients, measured within the previous 3 years, were used to compute BP variability as standard deviation (SD), coefficient of variation (CV) and average real variability (ARV) of systolic BP (SBP). Serum creatinine was used to estimate glomerular filtration rate (eGFR) using CKD-EPI algorithm. CKD was defined as eGFR < 60 ml/min/1.73m 2 . Results: The prevalence of CKD in our study population was 20.8%. CKD patients had higher maximum SBP (160 ± 20 vs 147 ± 23 mmHg, p = 0.028), SD of SBP (11 ± 4 vs 15 ± 7 mmHg, p = 0.016), CV of SBP (0.16 ± 0.04 vs 0.1 ± 0.02, p = 0.002) and ARV of SBP (19 ± 8 vs 14 ± 6 mmHg, p = 0.041). In multivariable logistic regression model, maximum SBP [OR (95% CI), 1.68 (1.12 – 3.1), p = 0.037], SD of SBP [1.21 (1.08 – 2.54), p = 0.031] and CV of SBP [1.31 (1.04 – 3.43), p = 0.023] were independently associated with CKD. ARV of SBP was not associated with CKD [1.48 (0.89 – 4.01), p = 0.11]. Conclusions: Visit-to-visit BP variability may be an independent determinant of CKD in T2DM patients in our study population.